Indirect electrochemical reduction of carbon dioxide to carbon nanopowders in molten alkali carbonates: process variables and product properties - Ijije, Happiness V.; Sun, Chenggong; Chen, George Zheng (Elsevier, 2014)
Carbon was deposited on a mild steel cathode during electrolysis in the molten mixture of Li2CO3 and K2CO3 (mole ratio: 62:38) under CO2 or mixed N2 and CO2 atmospheres at 3.0–5.0 V and 540–700 °C. In a three-electrode cell, cyclic voltammetry was applied on a platinum working electrode to study the reduction and deposition processes. A two-electrode cell helped correlate electrolysis variables, e.g. temperature and voltage, with the deposition rate, current efficiency, and properties of the deposited carbon powders. High current efficiency (>90%) and deposition rate (>0.11 g cm−2 h−1) were achieved in the study. Elemental analysis of the electro-deposits, following washing with HCl solutions (2.3–7.8 mol L−1), showed carbon as the dominant element (75–95 wt.%) plus oxygen (5–10 wt.%) and small amounts of other elements related to materials of the electrolytic cell. Thermogravimetry detected fairly low onset combustion temperatures (310–430 °C), depending on the electrolysis and acid washing conditions. Amorphous and various nanostructures (sheet, rings and quasi-spheres) were revealed by electron microscopy in carbon samples deposited under different process conditions. The specific surface area of the carbon deposited at 5.0 V and 540 °C was as high as 585 m2 g−1. An analysis of the energy consumption suggests several ways for efficiency improvement so that the electrolytic carbon from CO2 will become commercially attractive.